Classroom Games: Trading in a Pit Market 2.0 - Gunther Markwardt; André Seidel; Marcel Thum (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2016)
We have developed a computerized version of Charles Holt's classical market game that can be used even in classes with a large audience. The Pit market game gives students intuitive access to the interaction of supply and demand in real-world markets. Even though trade can take place at non-uniform prices in the classroom game, the average price and the quantity traded are usually very close to the equilibrium values predicted by supply and demand curves. The classroom game can also be used for a lively discussion about the efficiency of markets or to show the consequences of taxes and regulatory interventions.
urn:nbn:de:bsz:14-qucosa-210692
Keywords: A22; C88; D01; D40; 330; Pit Market; Market Game; Classroom Game; Economic Education; Supply and Demand; Pit Market; Angebot und Nachfrage; Marktspiel